PENGARUH KOMPETENSI SDM DAN MOTIVASI PEGAWAI TERHADAP PELAKSANAAN PENGAWASAN AMBIEN DI KOTA TANGERANG - Ade Burhanudin; Misbah Nurhafizah (Gapenas Publisher, 2021)
Tangerang City Government should also intensely monitor the ambient air in the city of Tangerang to improve oversight performed by existing employees in the Environmental Management Agency (BLH). Indeed, at this time the number of employees assigned to conduct surveillance in order to monitor the ambient in Tangerang are quite spacious, very limited, so that not all points that have a high potential of air pollutants can be placed air pollution monitoring tool.On the basis of the above reasoning, the researchers made the following thesis title: